2014
DOI: 10.1289/ehp.1308038
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Green Spaces for Children: A Cross-Sectional Study of Associations with Sedentary Behavior, Obesity, Asthma, and Allergy

Abstract: Background: Green spaces have been associated with both health benefits and risks in children; however, available evidence simultaneously investigating these conflicting influences, especially in association with different types of greenness, is scarce.Objectives: We aimed to simultaneously evaluate health benefits and risks associated with different types of greenness in children, in terms of sedentary behavior (represented by excessive screen time), obesity, current asthma, and allergic rhinoconjunctivitis.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
240
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(261 citation statements)
references
References 51 publications
11
240
1
9
Order By: Relevance
“…A more recent study in Spain confirmed these conclusions and showed that living in greener residential areas and living in closer proximity to forests was linked with less sedentary time and reduced risks of overweight and obesity in children (Dadvand et al 2014a).…”
Section: Reduced Prevalence Of Obesity and Type 2 Diabetesmentioning
confidence: 76%
“…A more recent study in Spain confirmed these conclusions and showed that living in greener residential areas and living in closer proximity to forests was linked with less sedentary time and reduced risks of overweight and obesity in children (Dadvand et al 2014a).…”
Section: Reduced Prevalence Of Obesity and Type 2 Diabetesmentioning
confidence: 76%
“…Mental health outcomes are reported for both adults and children (Dadvand et al, 2014Wu et al, 2014;Zhang et al, 2014), and for both men and women (Teas et al, 2007). Improvements derived from recreation and tourism have received particular attention (Kühnel and Sonnentag, 2011;Dolnicar et al, 2012;Chen and Petrick, 2013;Bimonte and Faralla, 2015;Coghlan, 2015;Zuo et al, 2015;Chen et al, 2016;Uysal et al, 2016).…”
Section: Mental Health Outcomesmentioning
confidence: 99%
“…Também, o ambiente em que a criança e o adolescente estão inseridos são fatores determinantes para sobrepeso/obesidade. Na Espanha, escolares que residem em áreas mais arborizadas apresentam menor prevalência de tempo de tela e de sobrepeso/obesidade, sugerindo que os fatores ambientais devem ser levados em consideração para a promoção da saúde de crianças e adolescentes 25 .…”
Section: Métodounclassified